2003
DOI: 10.3354/ame030103
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variations in viral distributions in the anoxic Cariaco Basin

Abstract: Virus-like particles (VLP), collected from the permanently anoxic Cariaco Basin between 10 October 1996 and 2 November 1999, were enumerated in water column and sediment trap samples. Vertical distributions of VLP from 18 depths between 7 and 1310 m generally corresponded to those of bacterial abundance and bacterial net production (BNP), with primary maxima consistently found in surface waters and midwater maxima near the O 2 /H 2 S interface. Temporal variations in VLP concentrations (0.81 to 630 × 10 8 VLP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 44 publications
(76 reference statements)
3
59
1
Order By: Relevance
“…Peaks in virus concentrations occurred at a depth of 7 m, which approximately corresponds to the position of the thermo-halocline in Bundera Sinkhole. This is consistent with previous observations of virus accumulations at physical transition zones, including thermoclines and oxyclines, within stratified water columns (Taylor et al 2003).…”
Section: Stratification Of the Virus Communitysupporting
confidence: 82%
“…Peaks in virus concentrations occurred at a depth of 7 m, which approximately corresponds to the position of the thermo-halocline in Bundera Sinkhole. This is consistent with previous observations of virus accumulations at physical transition zones, including thermoclines and oxyclines, within stratified water columns (Taylor et al 2003).…”
Section: Stratification Of the Virus Communitysupporting
confidence: 82%
“…Previous studies have also found peaks in concentrations of prokaryotes and viruses at transition zones in stratified aquatic environments, including peaks in the thermocline (Weinbauer et al 1995) and oxycline (Taylor et al 2003) of oceanic environments, and in the metalimnion of stratified lakes that have either an oxic (Bettarel et al 2003) or an anoxic (Weinbauer & Hofle 1998a) hypolimnion. In the latter 2 reports, significant differences in FVIC were also found between the epi-and hypolimnion.…”
Section: Spatial Patterns Of Prokaryotes Viruses and Fvicmentioning
confidence: 99%
“…5). A similar phenomenon was described by Taylor et al (2003) for variations of viral particles and prokaryotic abundance between three layers (oxic, transitional, and hypoxic) of the water column in Cariaco Basin. These authors found viral distribution to be marked by an environmental oxygen gradient, which was clearly reflected in VP-ratios; the higher proportions corresponded to the hypoxic zone.…”
Section: Discussionmentioning
confidence: 70%
“…The methodology utilized in this research (i.e. fixation with glutaraldehyde and storing at 4ºC) is the most common method used to preserve and store viruses for determining their abundance in aquatic ecosys- Fuhrman, 1998;Chen et al, 2001;Hewson et al, 2001;Culley and Welschmeyer, 2002;Taylor et al, 2003;Corinaldesi et al, 2003;Glud and Middelboe, 2004;Lunau et al, 2005;Vanucci et al, 2005). Nevertheless, this methodology is becoming controversial because there is evidence showing that it can underestimate viral abundance (Brussaard, 2004;Wen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation